Effect of Alkaline Treatment on the Tensile Strength and Hardness of Pineapple Fiber Reinforced Epoxy Resin - VIJIYAKUMAR, NAVINN; DR. MOHD YUSSNI BIN HASHIM (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This research is about fabricating a composite material using pineapple leaf fiber (PALF) reinforced epoxy resin. To fulfil the objective, different concentration of alkaline treatment on pineapple leaf fiber was applied. The treated pineapple fibers were then reinforced with epoxy resin. The prepared samples were then tested mechanically to achieve maximum improvement in mechanical properties. The composite material is produced by open mold technique by applying mold release agent to the specimens which compromise of 4 different material compositions such as pure PALF,2% alkaline treated PALF, 6% alkaline treated PALF, and 10% alkaline treated PALF coated with epoxy resin mixture with the ratio of 2:1. After the composite samples were obtained, they were tested mechanically to assess the material’s strength and indentation resistance. Based on the results obtained from the mechanical test, the sample with the optimal ratio was selected to fulfil this study.